Cardiac Resynchronization Therapy Reduces Metaboreflex Contribution to the Ventilatory Response in Heart Failure Population - Jérémie Jaussaud; Laurie Aimable; Pierre Bordachar; Pierre Dos Santos; Laurent Barandon; Philippe Ritter; Raymond Roudaut; Hervé Douard (Cardiology Research and Practice)
Background. Metaboreflex overactivation has been proprosed to explain exaggerated hyperventilation in heart failure population. We investigated the metaboreflex activation after cardiac resynchronization therapy (CRT). Methods. 10 heart failure patients (mean left ventricular ejection fraction (LVEF) 27±4%) schedulded for CRT implantation were prospectively studied. At baseline and after 6 month follow up two maximal cardiopulmonary exercise tests with and without regional circulatory occlusion (RCO) during recovery were performed. RCO was achieved by inflation of bilateral upper thigh tourniquets 30 mmHg above peak systolic blood pressure during 3 minutes after peak exercise. Metaboreflex contribution to the ventilatory response was assessed as the difference in ventilatory data at the third minute during recovery between the two tests (Δ). Results. Patients had enhanced VE/VCO2 slope (40±9) and an evident metaboreflex contribution to the high ventilatory response (ΔVE: 3±4 L/min; 𝑃=0.05, ΔRR: 4.5±4/min; 𝑃=0.003 and ΔVE/VCO2: 5.5±4; 𝑃=0.007). 6 months after CRT implantation, NYHA class, LVEF, peak VO2 and VE/VCO2 were significantly improved (1.4±0.5; 𝑃<0.001, 42±7%; 𝑃<0.001, 16.5±3 mL/kg/min; 𝑃=0.003; 33±10; 𝑃=0.01). Metaboreflex contribution to VE, RR, and VE/VCO2 was reduced compared with baseline (𝑃=0.08, 𝑃=0.01 and 𝑃=0.4 resp.). Conclusion. 6 months after CRT metaboreflex contribution to the ventilatory response is reduced.